Validation of a Dutch version of the Geriatric Oral Health Assessment Index (GOHAI-NL) in care-dependent and care-independent older people - Niesten, Dominique (BMC Geriatr, 2016)
BACKGROUND: The GOHAI is a frequently used instrument to measure oral health-related quality of life (OHRQoL) of adults, in particular older people. The aim of this study was to translate the original English version of the GOHAI into a Dutch version (GOHAI-NL), and to test the validity and reliability of the GOHAI-NL in care-independent and care-dependent older people. METHODS: The GOHAI questionnaire was translated into Dutch, discussed by an expert panel, back-translated to the original, pilot-tested and assessed for cognitive and conceptual equivalence. The resulting GOHAI-NL was tested in a groups of care-independent (Group A, n = 109, mean age 73.1 ± 5.4 years) and care-dependent (Group B, n = 118, mean age 85.6 ± 7.0. years) cognitively alert people of 65 years and over. Psychometric properties including reliability (internal consistency, item-total, item-dimension, dimension-total, inter-item correlation, and test-retest stability), and validity (convergent, discriminant, known-group), and floor and ceiling effects were assessed. RESULTS: Internal consistency was confirmed by Cronbach’s alphas of 0.86 (group A) and 0.80 (group B). Item-total score correlations were between 0.4 and 0.7 except for item 3 in group A (0.34) and B (0.08) and for item 12 in group A (0.20). Item-dimension and dimension-total correlations were between 0.30 and 0.78 and around 0.7 respectively for the dimensions ‘physical functioning’ and ‘psychosocial functioning’, but lower for the dimension ‘pain and discomfort’ with item-dimension correlations between 0.13 and 0.44. Average inter-item correlations were 0.34 ± 0.11 (group A) and 0.33 ± 0.08 (group B). Test-retest correlation of the total score (GOHAI-ADD) was 0.88 in group A (ICCs: 0.62 - 0.88) and 0.93 in group B (ICCs: 0.64 – 0.91). Significant correlations in the expected direction were found between GOHAI and most oral health-related variables except for presence of caries in group A, and perceived general health, prosthodontic status and number of natural teeth in group B. No floor or ceiling effects were detected at GOHAI-ADD level; however ceiling effects did occur at dimension level. CONCLUSION: The GOHAI-NL has satisfactory reliability and validity and can be used to measure OHRQoL in Dutch care-dependent and care-independent older people. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12877-016-0227-0) contains supplementary material, which is available to authorized users.